Experimental assessment of low-temperature martensite transformations in Ni-rich polycrystalline Ni-Ti alloys - Moreno-Gobbi, Ariel; Silva, Paulo Sergio; Nespeque Correa, Diego Rafael; Milá, Alfredo Masó; Muñoz Chaves, Javier Andrés; Grandini, Carlos Roberto [UNESP]; Macedo Dos Santos, Rafael Formenton; Moreira Afonso, Conrado Ramos (Elsevier, 2022)
Ultrasonic velocity and attenuation measurements of a commercially available Ni-rich polycrystalline Ni-Ti alloy were simultaneously obtained upon cooling from room temperature (RT) down to 130 K. The anelastic spectra show multiple anomalies in both velocity and attenuation curves, which evidence a complex nature of structural rearrangements exhibited by Ni-Ti alloy, associated with relaxations and phase transformations. In particular, some evident anomalies at 285 and 180 K, not previously exploited using ultrasonic measurements on Ni-rich polycrystalline Ni-Ti alloy, were associated with austenite to pre-martensitic (B2 → R) and pre-martensitic to martensitic (R → B19') phase transitions, respectively. The peculiar temperature separation between these transformations was interpreted based on chemical composition and the Ni-Ti alloy microstructure evolution. X-ray diffraction (XRD), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) were also used to add complementary results about phase transformations and thermal events exhibited by Ni-Ti alloy at low temperatures. XRD, Rietveld refinement, SEM and transmission electron microscopy (TEM) analyses confirm the coexistence of the austenite B2, martensite B19', and Ni4Ti3 phases at RT. DSC measurements indicated reversible two-stage martensitic transitions involving B2 → R → B19' phase transformations at similar temperatures than the observed from ultrasonic anomalies. Besides that, several anelastic relaxation events identified around the phase transitions reveal the occurrence of complex physical mechanisms, such as accommodation of the twinned R-phase and martensite domain walls, twinning boundaries mobility, and the coupling between stress-induced dislocation motion and interstitial diffusion, not reported simultaneously in the literature. The ferroelastic nature of martensite and pre-martensite phase transformations was confirmed for a commercially available Ni-rich polycrystalline Ni-Ti alloy studied in this work.
Keywords: Cryogenic temperature; Martensitic transformations; Ni-Ti alloy; Thermal properties; Ultrasonic characterization